Effect of Aloe-Vera on Liver Functions in Dog - Muhammad Asif Wisal, Shamsuddin Bughio, Muhammad Aarab, Hina Mahreen, Saniya Soomro, Saeed Ahmed Mirani, Muhammad Shah, Abdul Kabir, Nida Khanim, Aqib Khan (Pakistan Journal of Medical & Health Sciences, 2022)
Aloe vera is one of the most important plant used in modern science and has gained popularity in homeopathy and conventional medicine. Recent studies on rodents have shown its effect on liver. Therefore, current study was planned to assess the effects of Aloe Vera gel on liver function in normal and induced hyperglycaemic dogs. Aloe Vera gel was administrated orally in dogs (n = 12). The experimental period was divided into two phases. In each phase dogs were divided into three group’s i-e., A, B and C. In phase-1, group A was given only basal diet and kept as a control. Whereas group B was treated with Aloe vera gel at the therapeutic dosage of 500mg/kg B.W with basal diet, while group C was treated higher dosage regimen of 1000mg/kg B.W with basal diet once daily for 07 consecutive days. After 21 days washout period, in Phase-2, group A was fed basal with high carbohydrate diet and kept as a control. Whereas group B and C was administered Aloe vera gel at therapeutic dosage regimen of 500mg/kg B.W and 1000mg/kg B.W with basal with high carbohydrate diet once daily for 07 consecutive days respectively. In both phases, blood samples were collected at 0, 2, 6, and 10hr from day 1 to day 7, daily and on 10th and 14th day following Aloe vera treatment and analysed for biochemical parameters including serum Total Protein, Albumin, Globulin, Alanine aminotransferase, Aspartate aminotransferase, Alkaline Phosphatase and Bilirubin. Results revealed significant (P<0.05) decrease in biochemical parameters at therapeutic dosage of 500mg/kg as well as in higher dosage regimen of 1000mg/kg B.W against control. During this study in both phases all biochemical parameters decreased (P˂0.05) at 0, 2, 6 and 10hr from Day 1-14 post Aloe vera treatment. All biochemical parameters did not return to the pre-treatment values following the discontinuation of Aloe vera gel on 10th and 14th day of its treatment. It has been concluded from the current study that, the Aloe vera administration at the therapeutic dosage of 500 mg/kg B.W orally is adequate to reduce increased level of these biochemical parameters in dogs. Keywords:Aloe-vera, Liver, Function Test, Dog